Empowerment of Millennial Farmers in Increasing Farmers Welfare in the Industrial 4.0 Era and Towards the Society 5.0 Era - Zulpardiasyah Zulpardiasyah; Budi Eko (Journal Research of Social Science, Economics, and Management, 2022)
Indonesia as an agricultural country seems to be disappearing soon, but this situation is supported by the decline in the number of young farmers due to the subsequent activation of farmers. This research aims to improve welfare and create digital technology innovations in the role of young entrepreneurs in the millennial agricultural community. The method used is a literature review study method with a qualitative approach. The literature review method was chosen because it can be seen from the location of data collection. Based on the research results, revolution means very fast change. This revolution began with the Industrial Revolution 1.0 which was marked by the creation of the steam engine. This means the emergence of tools that change the power of humans and animals. Finally, Industry 4.0 has arrived. It is characterized by intelligent engineering, human-machine connectivity, and the Internet as the foundation of progress. Some call the Industrial Era 4.0 an era of turmoil.